STRUCTURAL EQUATION MODELLING OF PURCHASING MANAGEMENT SKILLS TO BUYER AND SELLER RELATIONSHIPS - หงษ์วิจิตร, กฤษณ; หงษ์วิจิตร, สุวรรณี (Modern Management Frontier Journal, 2017)
The purposes of this research were 1) to analyze structural equation modelling of purchasing management skills to buyer and seller relationship and 2)to confirm factors confirmation analysis of purchasing management skills. Data collection from Purchasing Management in 1st tier Automotive parts industry 242 firms. Instrument for data collection in this quantitative research is questionnaire. Data analysis used Structural Equation modeling. The result found purchasing management skill has positive relationship with buyer and seller relationship and found Technical skills, Interpersonal skills, Internal enterprise skills, External enterprise skills and Strategic business skills those is all element of purchasing management skills.